2018
DOI: 10.1080/1828051x.2018.1448726
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and nano-propolis in animal production and health: an overview

Abstract: Nanotechnology is the science and technology of small and specific things that are <100 nm in size. Because of the size of nanomaterials, new changes in their chemical and physical structure may occur, and indicate higher reactivity and solubility. Many of nanotechnology applications in food and agricultural production are being developed in research and development settings. Global challenges are related to animal production, including environmental sustainability, human health, disease control, and food secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…In the study conducted by Katanic et al [ 52 ] using spirea (Filipendula Ulmaria) extract to eliminate the side effects of CP, it was reported that CP significantly increased ALT, AST, and ALP values, which are among liver function tests, and creatinine and BUN values, which are among renal function tests, compared to the control group; on the other hand, the aforementioned extract (derived from the root area) decreased these parameters compared to the group to which CP was administered alone, but did not decrease the total protein, which is similar to the present study. The fact that propolis and NP had therapeutic effects against the negative effects of CP on blood parameters was associated with effective antioxidant compounds in their structure [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Katanic et al [ 52 ] using spirea (Filipendula Ulmaria) extract to eliminate the side effects of CP, it was reported that CP significantly increased ALT, AST, and ALP values, which are among liver function tests, and creatinine and BUN values, which are among renal function tests, compared to the control group; on the other hand, the aforementioned extract (derived from the root area) decreased these parameters compared to the group to which CP was administered alone, but did not decrease the total protein, which is similar to the present study. The fact that propolis and NP had therapeutic effects against the negative effects of CP on blood parameters was associated with effective antioxidant compounds in their structure [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when examining the Bax/Bcl-2 rate, it was determined that there were significant differences between CP + NP-30 and propolis groups in terms of the liver and kidney tissues and the CP + NP-30 group gave effective results by significantly reducing the Bax level in tissues ( Figure 3 and Figure 6 ). According to the results acquired, the fact that especially the second dose (30 mg/kg BW) of NP was much more effective than free propolis (100 mg/kg BW) at the cellular level was associated with the significant increase in propolis activity by nanotechnology, which thus made it possible to obtain better results despite using lower doses of propolis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other antimicrobial components in the nanoencapsulated forms could be even more efficient against pathogens. For example, natural antimicrobials from propolis showed better antimicrobial activity when they were in the form of nanosized particles [118].…”
Section: Use Of Polyphenol-loaded Nanoparticles In Food Processingmentioning
confidence: 99%
“…Propolis, a bee glue, is collected by honey bees from numerous plant flowers, and due to its unique biological attributes such as antibacterial, antifungal, and antiviral activities against several microorganisms, anti-inflammatory, antiulcer, antitumor, and immune-stimulating activities, it received great attention by the researchers and scientists [12,13]. Several studies indicated that propolis is composed of various valuable bioactive compounds such as alcohols, aldehydes, aromatic acids and esters, flavanones, flavones, hydrocarbon esters, ethers, hydroxyl and keto waxes, ketones, terpenoids, steroids, sugar, several vitamins (e.g., B, C, and E), resins, and silicon [14,15].…”
Section: Introductionmentioning
confidence: 99%